Argumentation and modelling skills in secondary school students: the need for a paradigm shift in Mathematics Education in Chocó, Colombia - Wilmer Ríos Cuesta (Universidade Federal do Oeste da Bahia, 2020)
In this study we present a documentary review of 50 works that offer us an opportunity to address some of the problems of education in the department of Chocó, in Colombia, where the results of the standardized tests that the Ministry of National Education carries out show that students present difficulties in the three competencies that the Saber test evaluates. On the other hand, we find a preference for the transmissionists model and for memorizing content. To address this problem, we look at two competencies: argumentation and modelling. Argumentation allows us to remove doubts about a statement and modelling has a high cognitive demand that requires, connecting and relating data and identifying regularities that allow us to model a phenomenon. The integration of these two skills into classroom practices offers an alternative to teachers for a paradigm shift in the education of students in Chocó.